Intergroup contact and team functioning among nursing students: the mediation role of intergroup anxiety - Marletta, Giuseppe; Sarli, Leopoldo; Caricati, Luca; Mancini, Tiziana (Acta Biomedica Atenei Parmensis, 2017)
Background and aim. Background and aim of the work. The improvement of team effectivity is one of the main concerns for healthcare organizations. Moreover, healthcare organizations must cope with increasing multicultural composition of both workforce and patients. The intergroup contact theory suggests that frequent and positive face-to-face contact among professionals or students with different cultural heritage can help to reach both increasing team effectiveness and adequate care in a multicultural setting. The aim was then to verify whether intergroup contact during practical training would decrease intergroup anxiety and then increase team functioning. Methods. A cross-sectional design was used in which a questionnaire was delivered to 83 nursing students. Results. According to the intergroup contact theory, frequent and positive contact with non-native professionals decreased the intergroup anxiety which, in turn, increased prejudice and, more importantly, decreased team functioning. Moreover, intergroup anxiety showed a complete mediation effect on the relations between intergroup contact during practical training and both negative attitude toward immigrants and team functioning. Conclusions. Intergroup contact with non-native professionals or students during practical training is able to indirectly decrease prejudice and improve team functioning by lowering the anxiety that is aroused by encounter with non-native individuals.